2020
DOI: 10.1038/s41598-020-76676-0
|View full text |Cite
|
Sign up to set email alerts
|

A natriuretic peptide from Arabidopsis thaliana (AtPNP-A) can modulate catalase 2 activity

Abstract: Analogues of vertebrate natriuretic peptides (NPs) present in plants, termed plant natriuretic peptides (PNPs), comprise a novel class of hormones that systemically affect salt and water balance and responses to plant pathogens. Several lines of evidence indicate that Arabidopsis thaliana PNP (AtPNP-A) affects cellular redox homeostasis, which is also typical for the signaling of its vertebrate analogues, but the molecular mechanism(s) of this effect remains elusive. Here we report identification of catalase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…It is important to note that RCA has been previously identified as a strong interactor of the AtPNP-A protein (lacking the signal peptide) in the Yeast Two-Hybrid assay [ 24 ], which is in accordance with our kinetic analyses. Furthermore, RCA was also proposed as a putative binding partner of pAtPNP-A based on cross-linking experiments performed in MCPs, followed by affinity chromatography and mass spectrometric identification [ 24 , 26 ]. Finally, our recent study indicates AtPNP-A localizes into chloroplasts [ 24 ], which may further support potential biological relevance of its interaction with a stromal RCA protein.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is important to note that RCA has been previously identified as a strong interactor of the AtPNP-A protein (lacking the signal peptide) in the Yeast Two-Hybrid assay [ 24 ], which is in accordance with our kinetic analyses. Furthermore, RCA was also proposed as a putative binding partner of pAtPNP-A based on cross-linking experiments performed in MCPs, followed by affinity chromatography and mass spectrometric identification [ 24 , 26 ]. Finally, our recent study indicates AtPNP-A localizes into chloroplasts [ 24 ], which may further support potential biological relevance of its interaction with a stromal RCA protein.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, RCA was also proposed as a putative binding partner of pAtPNP-A based on cross-linking experiments performed in MCPs, followed by affinity chromatography and mass spectrometric identification [ 24 , 26 ]. Finally, our recent study indicates AtPNP-A localizes into chloroplasts [ 24 ], which may further support potential biological relevance of its interaction with a stromal RCA protein. Although the data reported here are of preliminary nature and the biological significance of this interaction is still to be elucidated, this increasing body of evidence has potential implications of the interaction between PNPs and RCA for plant development and stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Swiezawska et al, 2015(Swiezawska et al, , 2017 and Japanese morning glory (Szmidt-Jaworska et al, 2009) and in the monocot grass model Brachypodium (Swiezawska et al, 2020), as well as in a human immune-responsive protein IRAK3 (Freihat et al, 2019), have demonstrated the robustness of this approach and its significance in biological discoveries across different systems. Furthermore, the method enables candidate selections for follow-up in vivo and in planta studies that will eventually reveal the biological roles of these functional centers such as those reported in Joudoi et al (2013), Shen et al (2019), Vaz Dias et al (2019, Angkawijaya et al (2020), Lee et al (2020), andTurek et al (2020). We foresee that emerging experimental data will inform and strengthen motif refinement efforts, and enable the development of modern machine learning techniques that incorporate multiple features ranging from the classical physicochemical properties of protein domains and protein-protein interaction (PPI) networks to GO based function predictions, to not only automate annotations for uncharacterized proteins, but also to identify hidden functional centers in complex multi-functional proteins (Rifaioglu et al, 2019;Bonetta and Valentino, 2020;Cai et al, 2020;Littmann et al, 2021).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The PNP-binding site (green), the ABA-binding site (blue), and the H-NOX center (orange) are represented, with the key amino acids involved in interactions with their ligands shown in dark grey. The PNP-binding site is implicated in H 2 O 2 homeostasis, regulation of protoplast volume, defense response against pathogens, and photosynthesis, which could be achieved through interactions of PNP-A (TAIR: At2g18660) with PNP-receptor 1 (TAIR: At1g33612), catalase 2 (TAIR: At4g35090) or Rubisco activase (TAIR: At2g39730) [106] , [107] , [108] , [109] , [110] . The ABA-binding site of an outward rectifying potassium channel AtGORK (TAIR: At5g37500) is involved in K + transport in guard cells [95] .…”
Section: Introductionmentioning
confidence: 99%